2017
DOI: 10.1074/jbc.m117.812701
|View full text |Cite
|
Sign up to set email alerts
|

Peropsin modulates transit of vitamin A from retina to retinal pigment epithelium

Abstract: Edited by Velia M. FowlerPeropsin is a non-visual opsin in both vertebrate and invertebrate species. In mammals, peropsin is present in the apical microvilli of retinal pigment epithelial (RPE) cells. These structures interdigitate with the outer segments of rod and cone photoreceptor cells. RPE cells play critical roles in the maintenance of photoreceptors, including the recycling of visual chromophore for the opsin visual pigments. Here, we sought to identify the function of peropsin in the mouse eye. To thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…RPE expresses factors required for lipoprotein intake, cholesterol and lipoprotein synthesis and secretion, as well as reverse cholesterol transport (RCT) [94]. Phagocytosis and degradation of the POSs are the principal lipid source for the RPE [95], as well as processing and recycling back to the photoreceptors of vitamin A and of DHA [96,97]. Moreover, excess cholesterol is loaded on HDLs by ABC transporters and, then, removed, or it is also secreted in VLDL-like lipoproteins basolaterally into Bruch's membrane where it forms drusen [98].…”
Section: Discussionmentioning
confidence: 99%
“…RPE expresses factors required for lipoprotein intake, cholesterol and lipoprotein synthesis and secretion, as well as reverse cholesterol transport (RCT) [94]. Phagocytosis and degradation of the POSs are the principal lipid source for the RPE [95], as well as processing and recycling back to the photoreceptors of vitamin A and of DHA [96,97]. Moreover, excess cholesterol is loaded on HDLs by ABC transporters and, then, removed, or it is also secreted in VLDL-like lipoproteins basolaterally into Bruch's membrane where it forms drusen [98].…”
Section: Discussionmentioning
confidence: 99%
“…It mediates extracellular diffusion of retinoids during the operation of the retinoid cycle, transporting alltrans-retinol and 11-cis-retinal between the photoreceptors and the RPE (Gonzalez-Fernandez, 2003). A recent study suggested that IRBP may not be the only vehicle and peropsin may also transport all-trans-retinol from the neural retina to RPE (Cook et al, 2017). Human organic anion transporting polypeptide 1A2 (OATP1A2) has been recently found to be expressed at the apical membrane of RPE, where it facilitates the cellular uptake of all-trans-retinol into the RPE cells (Chan et al, 2015).…”
Section: The Canonical Visual Cyclementioning
confidence: 99%
“…Unlike RGR, RRH has retained the DRY sequence within the ionic lock switch as well as other GPCR features necessary for structure, G protein signaling, and retinal binding ( Figure 2c ). While no functions for RRH have been established in mammals beyond photoisomerization and retinal transport, it is interesting that arachnid RRH is in an active, potentially signaling state in the dark and is suppressed by light ( Cook et al, 2017 ; Nagata et al, 2018 ). Not only do these results suggest that RRH may have G protein signaling functions, but that the functions of RRH are conserved in all mammals, regardless of their lighting environment although decreased sequence constraint in subterrestrial/nocturnal mammals demonstrate a spectrum of biological selection.…”
Section: Resultsmentioning
confidence: 99%